2018
DOI: 10.36076/ppj.1.2018.73
|View full text |Cite
|
Sign up to set email alerts
|

The Termination Level of the Dural Sac Relevant to Caudal Epidural Block in Lumbosacral Transitional Vertebrae: A Comparison between Sacralization and Lumbarization Groups

Abstract: Background: Lumbosacral transitional vertebrae (LSTV) are a relatively common variant and have been considered as one of the reasons for back pain. It is not unusual for clinicians to encounter patients with LSTV who require caudal epidural block (CEB) for pain management. Objective: We investigated the termination level of the dural sac (DS) and anatomical features of the lumbosacral region relevant to CEB in patients with LSTV and compared these findings between sacralization and lumbarization groups. Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…The frequency distribution of level of dural sac termination as determined by MRI. Three previous studies reported that the S2 was the most frequent point of termination for the dural sac 8,11,16) . vel 1,6,12) , while the most frequent level of DS termination was at the middle one-third of S2 (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The frequency distribution of level of dural sac termination as determined by MRI. Three previous studies reported that the S2 was the most frequent point of termination for the dural sac 8,11,16) . vel 1,6,12) , while the most frequent level of DS termination was at the middle one-third of S2 (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Although earlier studies on the level of termination of the spinal cord and DS have been confined to cadavers and myelography, MRI has become a more accurate and convenient method by which to confirm early termination of the DS 16) . A study on the caudal epidural block demonstrated a significant difference in level of DS termination on MRI scans between sacralization and lumbarization groups 8) . Here, the mean caudal DS level in the lumbarization group (lower one-third of S2; 44.7%) was significantly lower than that in the sacralization group (lower one-third of the S1; 38.8%), and it has been reported that knowing the DS termination point could prevent injury to the dura or surrounding structures during caudal block 8) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El aspecto de seguridad de las técnicas es otro aspecto a tener en consideración. La vía caudal es una vía segura para evitar la punción dural (salvo en los hipotéticos casos de punción de quistes de Tarlov o un saco tecal descendido más allá de S2) y evitar posibles lesiones neurológicas derivadas de punciones de arterias espinales (31). La vía interlaminar es una vía segura para evitar lesiones neurológicas provocadas por punción de arterias radiculares e inyección de material embolígeno, aunque la punción dural y la subdural sigue constituyendo un riesgo (32).…”
unclassified